Efficacy of doxycycline in the treatment of early stages of mycosis fungoides: a randomized controlled trial. (19th May 2021) - El Sayed, H.; Shalaby, S.; Abdel-Halim, M. R. E.; Aboelfadl, D. M.; Samir, N.
Abstract: Background: Mycosis fungoides is the most common type of primary cutaneous T cell lymphomas. Doxycycline promoted apoptosis in different human malignant cell lines and in vivo models. Objectives: To test for the therapeutic efficacy of doxycycline in comparison to PUVA in early stages of classic MF and its effect on T cell apoptosis. Methods: Thirty-six patients were randomized into either: doxycycline 200 mg daily ( n = 18) or PUVA (3 weekly sessions) ( n = 18) for 12 weeks. The primary outcome (therapeutic efficacy) was defined in terms of objective response rate (ORR) which was measured according to changes in the modified severity weighted assessment tool (mSWAT). Results: Doxycycline achieved significantly less ORR (partial response) in comparison to PUVA (11.1%, 50%, respectively, p = .016). The percent reduction in mSWAT, CAILS, histopathology score and CD3 expression was significantly less in the doxycycline group ( p = .001, p = .001, p ˂ .001, and p = .004, respectively). Within the doxycycline group, changes in mSWAT and CAILS showed no correlation with changes in the CD3 or Bcl-2 expression. Gastric upset was significantly more encountered in the doxycycline group ( p = .001). Conclusion: Doxycycline is not suitable as a sole agent in the treatment of early stages of classic MF, acting mainly by anti-inflammatory rather apoptotic function. Register number: NCT03454945 (www.clinicaltrials.gov ).